Family–School Collaboration in Fostering Children's Character Through Religious and Moral Values - Raysha Amallia; Aslamiah Aslamiah; Novitawati Novitawati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The cultivation of moral and religious values in early childhood is a foundational component in fostering holistic character development. This literature study aims to analyze the role of early childhood education teachers, the influence of the family environment, the effectiveness of parent–teacher synergy, and the supporting and inhibiting factors in the internalization of moral and religious values. Employing a qualitative descriptive approach through literature review, this study synthesizes findings from peer-reviewed academic sources. The results indicate that ECE teachers play a strategic role as role models, facilitators, and motivators through methods such as habituation, storytelling, and value-integrated learning. Concurrently, the family particularly through democratic parenting and consistent religious practices contributes significantly to the moral development of children. The synergy between teachers and parents enhances the consistency of value internalization, especially when supported by collaborative programs, two-way communication, and digital parenting initiatives. However, challenges such as limited parental understanding, lack of educational resources, and negative digital influences hinder optimal collaboration. These findings underscore the necessity of effective communication, continuous teacher training, and active parental involvement to ensure the successful moral and religious education of young children.